Anisotropic fatigue behaviour of interbeded marble subjected to uniaxial cyclic compressive loads. Issue 6 (12th January 2020) - Wang, Yu; Gao, Shaohua; Liu, Dongqiao; Li, Changhong
Abstract: The work aims to experimentally investigate the anisotropic fatigue characteristics of marble with different bedding orientations using uniaxial fatigue experiments and posttest computed tomography (CT) scanning. The impacts of interbed orientation on the strength, deformation, fatigue life, and stimulated fracture pattern were systematically analysed. Results show that the axial, lateral, and volumetric strain curves present a three‐stage deformation and are influenced by the interbed orientation. The volumetric strain is maximum and minimum for a marble sample with 30 and 90° orientation, respectively, which is closely related to the failure mode. The crack pattern in the CT images is related to the interbed orientation; the crack density and scale are the largest for a 90° orientation sample and are the smallest for a 30° orientation sample. Good correlation has been established between the fatigue lifetime and the interbed orientation. It is suggested that anisotropic cyclic behaviours of marble is structurally dependent.